Echa działań wojennych w latach 1812-1814 na Dolnym Śląsku i Środkowym Nadodrzu od XIX do początków XXI wieku - Tomasz Nodzyński (In Gremium. Studies in History, Culture and Politics, 2014)
Echoes of War in the Years 1812-1814 in Lower Silesia and Middle Odra Area From the Nineteenth Century to the Early Twenty-First CenturyThe article shows the most important military and diplomatic actions during the Napoleonic expedition to Russia in 1812 and the events of the years 1813 to 1814 in the territory of Middle Odra (the Provinces of Silesia and Brandenburg). Draws attention to the differences in Polish and Prussian – German perspective of looking at the war from the years 1812 to 1815. Until 1945 predominated the cult of these events, in 1945-1989 largely ignored them in silence, since 1989 restored them to the collective memory, as a part of historical heritage, often attractive to tourists.